Characterizing PML/RAR? Isoforms of Acute Promyelocytic Leukemia (APL) in Malay Patients (Bangladesh Journal of Medical Science, 2014)
Aim: Reciprocal translocation between retinoic acid receptor alpha (RAR?) gene on chromo- some 17 and promyelocytic leukemia (PML) gene on chromosome 15 is the hallmark for acute promyelocytic leukemia (APL). Three different PML/RAR? isoforms have been described; S-form, L-form and V-form. Our aims were to characterize the different types of PML/RAR? iso- forms in Malay patients with APL and to determine the outcome of these different types of iso-forms. Materials and methods: RT-PCR analysis was performed on 20 patients recruited from hematology-oncology ward. RT-PCR detected fusion transcript of PML/RAR? in all patients. Results and Discussion: Of these patients, 65% (13 patients) exhibited L/V-form, and 35% (7 patients) S-form. Total white blood cell count (TWBC) was higher in L/V-form (25 x 109/l) compared to S-form (2.1 x 109/l) (p < 0.05). Five years survival rate was 100% and 33.3% for L/V-forms and S-forms respectively (p